1998
DOI: 10.1136/bmj.317.7153.241
|View full text |Cite
|
Sign up to set email alerts
|

Reduced fetal growth rate and increased risk of death from ischaemic heart disease: cohort study of 15 000 Swedish men and women born 1915-29

Abstract: Objective: To establish whether fetal growth rate (as distinct from size at birth) is associated with mortality from ischaemic heart disease. Design: Cohort study based on uniquely detailed obstetric records with 97% follow up over the entire life course and linkage to census data in adult life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
507
6
12

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 735 publications
(547 citation statements)
references
References 18 publications
19
507
6
12
Order By: Relevance
“…The association of larger birth size with increased cancer incidence in men found here is in the opposite direction to that found with circulatory diseases in this cohort 2 and in other studies. 3 Furthermore, the magnitude of the overall increase in cancer incidence in men observed here is approximately half the magnitude of the decrease in ischemic heart disease in the same cohort 2 (hazard ratio of 1.17 for cancer vs. 0.77 for IHD for 1,000 g increase in birth weight).…”
Section: Biologic Plausibilitycontrasting
confidence: 99%
See 1 more Smart Citation
“…The association of larger birth size with increased cancer incidence in men found here is in the opposite direction to that found with circulatory diseases in this cohort 2 and in other studies. 3 Furthermore, the magnitude of the overall increase in cancer incidence in men observed here is approximately half the magnitude of the decrease in ischemic heart disease in the same cohort 2 (hazard ratio of 1.17 for cancer vs. 0.77 for IHD for 1,000 g increase in birth weight).…”
Section: Biologic Plausibilitycontrasting
confidence: 99%
“…2 Detailed obstetric notes were kept, providing data on maternal age, birth order, birth weight and placental weight (recorded to the nearest 10 g) and birth length and head circumference (recorded to the nearest 0.5 cm). Ponderal index, a measure of weight relative to height in infants, was calculated as birth weight/length 3 (kg/m 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Intrauterine growth restriction (IUGR) is a major cause of perinatal mortality and morbidity1, 2, 3 and is associated with long‐term consequences, including impaired neurological development4 and increased risks of developing cardiovascular disease5 and metabolic syndrome6. There are no effective therapies to reverse IUGR, and antenatal management is aimed at determining the ideal time for delivery, sometimes very prematurely.…”
Section: Introductionmentioning
confidence: 99%
“…Hales and co-workers suggested that undernutrition during critical periods, leading to impaired development of b-cell function and muscle response to insulin, is the root cause of impaired glucose tolerance and diabetes -the 'thrifty phenotype hypothesis' (Hales et al, 1991;Barker, 1994). Many longitudinal studies have since provided supporting evidence for these hypotheses among diverse populations, mostly in high-income countries using data from historical cohorts (Hales et al, 1991;Leon et al, 1998;Bavdekar et al, 1999;Eriksson et al, 2001;Yajnik, 2001;Barker et al, 2002). This study, drawing on longitudinal birth cohort data, assessed levels of haemoglobin (Hb) A 1c in adolescence in relation to fetal growth rate in an urban Brazilian population.…”
Section: Introductionmentioning
confidence: 99%